Compensatory mutation partially restores fitness and delays reversion of escape mutation within the immunodominant HLA-B*5703-restricted Gag epitope in chronic human immunodeficiency virus type 1 infection. - Crawford, H; Prado, J; Leslie, A; Hué, S; Honeyborne, I; Reddy, S; van der Stok, M; Mncube, Z; Brander, C; Rousseau, C; Mullins, J; Kaslow, R; et al. (2007)
HLA-B*5703 is associated with effective immune control in human immunodeficiency virus type 1 (HIV-1) infection. Here we describe an escape mutation within the immunodominant HLA-B*5703-restricted epitope in chronic HIV-1 infection, KAFSPEVIPMF (Gag 162-172), and demonstrate that this mutation reduces viral replicative capacity. Reversion of this mutation following transmission to HLA-B*5703-negative recipients was delayed by the compensatory mutation S165N within the same epitope. These data may help explain the observed association between HLA-B*5703 and long-term control of viremia.